Peranan Guru dalam Pengelolaan Kelas untuk Meningkatkan Motivasi Belajar Siswa di Sekolah Dasar - Iskandar, Sofyan; Rosmana, Primanita Sholihah; Apriliani, Delia; Rahmawati, Hanny; Fauziyah, Nisa Nur (JURNAL SINEKTIK, 2025)
Classroom management is an important concept in school learning. This article provides an overview of the definition of classroom management, strategies that teachers can implement to manage the classroom, and the important role teachers play in ensuring successful learning. In addition, this article emphasizes the importance of classroom management to increase students' learning motivation and identifies barriers that may arise in classroom management during the learning process. By understanding the concept of good classroom management and implementing appropriate strategies, teachers can create a safe, comfortable learning environment and help improve students' motivation and well-being. This article uses a literature review method from relevant sources as well as interviews. Based on the results of the literature review, effective classroom management can increase students' motivation and enthusiasm for learning. We hope this article provides tips for teachers on how to increase student motivation through classroom management.